The effect of inflation on high technology exports - Aykaç, Selim; Pehlivanoğlu, M. Çağrı; Civelek, Mustafa Emre (Istanbul Commerce University, 2024)
This study aims to determine the relationship between inflation and exports of high technology products. Within the framework of the research model, the relationships between Inflation, Ease of Doing Business, Education Expenditures and High Technology Exports were analyzed. The research sample includes 5-year data of 130 different countries. Four hypotheses were formulated and tested in the study. As a result of the analyzes, all hypotheses were accepted. According to the hypotheses test results, inflation exerts negative effect on doing business; inflation has a negative impact on education expenditure; education expenditure has positive effect on doing business; doing business has positive effect on high technology exports. The results demonstrate that inflation reduces education spending and increases the difficulty of doing business in a country. Thus, one of the adverse consequences of inflation is a decrease in educational expenditure and an increase in the difficulty of doing business, which in turn has a negative impact on the export of high-tech goods. High-tech goods production and export are vital to a country's economic welfare. In societies where education spending is declining, human potential for creativity and self-improvement may be curtailed. This is a topic that requires further research across a range of disciplines.
Keywords: Inflation; Education Expenditure; High Technology Export; Doing Business